Estate planning among older Americans: The moderating role of race and ethnicity. Issue 3 (27th October 2019) - Choi, Shinae L.; McDonough, Ian M.; Kim, Minjung; Kim, Giyeon
Abstract: This study investigated whether race and ethnicity moderated the associations of bequest expectations to leave an inheritance and charitable giving with having a valid will among older Americans. Drawn from the 2014 Health and Retirement Study, we analyzed 13, 261 respondents using multilevel logistic regression with generalized linear mixed models. People with higher bequest expectations and more charitable giving were more likely to have a valid will. Ethnic minorities had much lower bequest expectations and much less charitable giving than non‐Hispanic Whites, controlling for socioeconomic indicators. Hispanics showed a stronger effect of bequest expectations but a weaker effect of charitable giving on having a valid will compared with non‐Hispanic Whites. Our findings reveal novel racial and ethnic disparities in engagement in estate planning among older adults and suggest alternative means are needed to promote interest in estate planning in later life depending on one's racial and ethnic background.